PENGARUH UNIT COST LAYANAN TERHADAP PENDAPATAN SEKOLAH DI TENGAH DINAMIKA LINGKUNGAN - Purwanto, Purwanto (AKTUAL, 2024)
This research aims to analyze the influence of service unit costs on school income amidst changing environmental dynamics. The research was conducted through a case study at one of the integrated private schools in Yogyakarta. Dynamic changes in the school environment, such as: trends in service demand, policy changes, pandemics, often encourage schools to adapt to change. Research data is in the form of financial reports and institutional profiles for 2005-2021. Analysis in the form of time series and cross section analysis (between service units). The research was conducted by regressing the influence of costs per unit of service on school admissions amidst environmental dynamics. Research was conducted using a qualitative approach with case studies for conceptual development. The research results found that changes in the school environment had an impact on the cost per unit of school services. The cost per unit of school services has a different effect on school revenues. Through analysis per service unit, schools can estimate the impact of changes in service units (changes in service scale, addition of new service units, deletion of service units and transfer of service units) on school revenues. The results of this study provide implications for the potential of a modular service unit system for managing school finances amidst environmental dynamics. The school consists of several school service units. The modular system makes school financial management easy to add, delete, and reconfigure to adapt to change.